2020
DOI: 10.1002/lt.25718
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, Transcriptional, and Functional Analysis of Liver Mesenchymal Stromal Cells and Their Immunomodulatory Properties

Abstract: The liver is an immunologically active organ with a tolerogenic microenvironment at a quiescent state. The immunoregulatory properties of the liver appear to be retained after transplantation because liver allografts can reduce alloresponses against other organs that are simultaneously transplanted. Mechanisms of this phenomenon remain unknown. Given the known immunomodulatory properties of mesenchymal stromal cells (MSCs), we hypothesized that liver mesenchymal stromal cells (L‐MSCs) are superior immunomodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…MSCs can reduce the activity of T-cells using different mechanisms, for example by secretion of indoleamine 2,3-dioxygenase (IDO), an enzyme capable of metabolizing the amino acid tryptophan to kynurenine. T-cells rely on this amino acid to become activated, and the depletion of tryptophan induces apoptosis or inhibiting their proliferation and differentiation by cell to cell contact, a process mediated by PD-L1 ( 101 , 102 ).…”
Section: Tolerance Mechanisms In the Liver Allograftmentioning
confidence: 99%
“…MSCs can reduce the activity of T-cells using different mechanisms, for example by secretion of indoleamine 2,3-dioxygenase (IDO), an enzyme capable of metabolizing the amino acid tryptophan to kynurenine. T-cells rely on this amino acid to become activated, and the depletion of tryptophan induces apoptosis or inhibiting their proliferation and differentiation by cell to cell contact, a process mediated by PD-L1 ( 101 , 102 ).…”
Section: Tolerance Mechanisms In the Liver Allograftmentioning
confidence: 99%
“…Adult liver-derived MSC are negative for human leukocyte Ag class II (HLA-II) and the co-stimulatory molecules, including CD80 and CD86, which can inhibit the proliferation of T cells activated by mitogen (34). Interestingly, liver graft-derived MSC have greater capacity to suppress allo-reactive T cell proliferation and cytotoxic degranulation than bone marrow-derived MSC (BM-MSC) (35), as well as significantly higher levels of immune-regulatory genes than adipose tissue-derived MSC and BM-MSC, that depend on programmed cell death ligand 1(PDL1) expression (36) for their ability to subvert T cell response.…”
Section: Intrahepatic Immune Cells Interact With Liver Parenchymal Cementioning
confidence: 99%
“…The detailed characterization of both the L-MSC and the A-MSC used in the current study was reported previously (Conley et al, 2020;Taner et al, 2020). Both types of MSCs demonstrated plastic-adherent characteristics and spindleshaped morphology when cultured in PL5% MSC media.…”
Section: Msc Characterizationmentioning
confidence: 77%
“…Given the liver's unique tolerogenic microenvironment (Taner et al, 2016(Taner et al, , 2017(Taner et al, , 2018, we had postulated that liver MSCs (L-MSCs) are superior immunomodulators than their counterparts isolated from other tissues. In fact, we demonstrated that L-MSCs inhibited alloreactive T cell proliferation better than MSCs isolated from adipose tissue (A-MSC) and bone marrow (BM-MSC) (Taner et al, 2020). Transcriptome analysis also demonstrated that the L-MSCs have significantly upregulated expression of genes and gene sets associated with immune regulation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation